Influencing factors for effective community ICT hubs. - Basaruddin, Suzana; Sutan Ahmad Nawi, Haslinda; Ahmad Shukor, Nur Syufiza; Jusoff, Kamaruzaman; Jahari, Nor Azah; Saleh, Hamdan (IDOSI Publications, 2010)
Government provides public ICT hubs to ensure that community is ICT literate. Selangor stategovernment sponsors public ICT hubs in order to address the digital divide issues especially in the rural area.This study was designed to determine the factors that influence the success and sustainability of ICT hubs thatwere provided by the Selangor State Government, Malaysia. Detailed analysis of 26 ICT hubs throughquestionnaires, interviews and observation were conducted. The results contributed to the formulation of 27influencing factors and were categorized to three-perspectives: technology (five factors); organizational (sixteenfactors); and environment (six factors).